Inhibition of Melanoma Cell Proliferation by Targeting Wnt/β-catenin Pathway through Sox4 RNA Interference - 蔡华华 倪安红 李雯 李家文 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
The effect of siRNA-mediated Sox4 gene silencing on Wnt/β-catenin signaling pathway of human malignant melanoma cell line A375 was investigated.Two types of dsRNA targeting Sox4 were constructed and transfected into A375 cells,and untreated cells and cells transfected with scramble RNA were used as blank control and negative control respectively.The expression levels of mRNA and protein of Sox4,Wnt3a,β-catenin and Wnt/β-catenin signaling target gene Survivin were detected after real-time PCR and Western blot respectively.MTT assay was used to measure cell proliferation after Sox4 knockdown.β-catenin/TCF transcription reporter assay was used for assessing Wnt/β-catenin signaling pathway activity.Our results showed that the two types of Sox4 siRNA were transfected into A375 cells successfully.As compared with untreated cells,Sox4 siRNAs had no significant influence on Wnt3a expression,and Sox4 siRNAs led to the decrease of β-catenin at protein level.Wnt/β-catenin signaling pathway activity was inhibited significantly.As a target of Wnt/β-catenin signaling,Survivin was decreased at both mRNA and protein levels,and cell proliferation was attenuated.Our study suggests that Sox4 may play an important role in Wnt/β-catenin signaling pathway in human malignant melanoma cells by regulating β-catenin protein level,indicating that Sox4 is involved in the progression of malignant melanoma through Wnt/β-catenin signaling pathway.